Opinions on Dental Erosive Lesions, Knowledge of Diagnosis, and Treatment Strategies among Norwegian Dentists: A Questionnaire Survey - Aida Mulic; Simen Vidnes-Kopperud; Anne B. Skaare; Anne Bjørg Tveit; Alix Young (Hindawi Limited, 2012)
This study aimed to investigate dentists' general experience, knowledge about diagnosis, and treatment of dental erosive wear in young adults. A questionnaire was sent to 1262 Norwegian public dental health-employed dentists. The response rate was 60%. Results indicated that most dentists recorded erosive wear, half of them used a specific scoring system, and half registered lesions at the tooth surface level. Lesions were reported most often on palatal surfaces of upper anterior teeth (79% of dentists), on occlusal surfaces of lower 1st molars (74%), and on upper 1st molars (32%). Half the dentists used clinical photographs for documentation and 60% made study models. While 40% reported more erosive lesions in males, 36% reported no gender differences. High intake of carbonated beverages and acidic juices were reported as the most common cause by 97% and 72% of the dentists, respectively. Only 21% of dentists recorded the patient's dietary history, and 73% never measured saliva secretion. The majority (78%) of the dentists treated patients with erosive wear themselves. In general, the survey suggests that the dentists are relatively up to date regarding the clinical recording, diagnosis, and treatment of dental erosive wear. However, dietary and salivary analyses were not given priority, and early, preventive treatment was lacking.